(untitled) (Sir Salimullah Medical College Journal, 2026)
Background: Perinatal asphyxia is one of the most common causes of neonatal mortality and morbidity. The most severe complication of PNA is HIE. Perinatal hypoxic-ischemic encephalopathy (HIE) occurs in 1 to 3% of term or near-term births as a result of hypoxic and/or ischemic insults during labor and delivery. Magnesium sulphate is cost-effective and readily available, and is easily administered in comparison to cooling therapy. The aim of the study. The aim of the study to assess effect of magnesium sulphate in Hypoxic ischemic encephalopathy. Methods: This was a Randomized controlled trial conducted in the Department of Neonatology, Sir Salimullah Medical College Mitford Hospital for a period of 18 (eighteen) months from January 2022 to June 2023. Term neonates who were admitted as Perinatal asphyxia with Hypoxic Ischemic Encephalopathy are the study population. All term inborn/outborn babies, reaching within 6 hours of delivery to Department of Neonatology, Sir Salimullah Medical College Mitford Hospital and fulfilling the operational definition of HIE stage II & III, were included. Experiment Group were given magnesium sulphate 250mg/kg/dose 3 times 24 hour apart within 6 hour of post-natal age with monitoring of vitals. Control group received similar supportive and symptomatic treatment (conventional therapy) with regular monitoring as experiment group. Baseline serum magnesium level was done before first dose then at day 2, day 3 before giving magnesium sulphate in experiment group & control group. Serum Mg level were measured by Vitros 5600 Micro-slide Biochemistry Analyzer (Made in USA). The system software determines the test results of patients automatically. Results: A total of 160 patients were randomized (80 in experiment group and 80 in control group). Both groups had similar baseline characteristics (P> 0.05) including severity of HIE. Median age of starting MgSO4 infusion is 5 hour. In experiment group frequency of seizure (single episode (33.3%), multiple episode (66.7%), time of control of seizure (<48 hrs (70%), >48 hrs (30%), abnormal neurologic status at discharge (36.7%), absent direct breast feeding at discharge (21.7%), the corresponding values in control group (38.3%), (61.7%), (61.7%), (38.3%), (35%), (23.3%). In experiment group duration of hospital stay (<7 day (25%), ³7 days (75%)), mortality (22.5%), the corresponding values in control group (20%), (80%), (20%). The differences were not statistically significant (P>0.05). Serum Mg level in experiment group, day 1 (0.72±0.14), day 2 (1.18±0.24), day 3 (1.64±0.28), in control group corresponding values are (0.74±0.18), (0.8±0.9), (0.84±0.17). The difference was not statistically significant in day 1 but significant in day 2 and day 3. Conclusion: Infusion of MgSO4 after birth did not improve features of HIE in newborn with PNA. There was higher trend of mortality observed in MgSO4 group although statistically not significant. Sir Salimullah Med Coll J 2025; 33: 117-124